Pancreatic cyst biopsy: Improvement in diagnosis with micro forceps biopsy. Issue 4 (5th February 2018) - Basar, Omer
Abstract : Clinician's Corner represents the opinions and views of the author and does not reflect any policy or opinion of the American Cancer Society, Cancer Cytopathology, or Wiley unless this is clearly specified.